Effects of SGLT2 Inhibitors and GLP-1 Receptor Agonists on Renin-Angiotensin-Aldosterone System - Puglisi, Soraya; Rossini, Alessandro; Poli, Roberta; Dughera, Francesca; Pia, Anna; Terzolo, Massimo; Reimondo, Giuseppe (Frontiers in Endocrinology, 2021)
Sodium-glucose cotransporters inhibitors (SGLT2-i) and GLP-1 receptor agonists (GLP1-RA) are glucose-lowering drugs that are proved to reduce the cardiovascular (CV) risk in type 2 diabetes mellitus (T2DM). In this process, the renin-angiotensin-aldosterone system (RAAS) is assumed to play a role. The inhibition of SGLT2 improves hyperglycemia hampering urinary reabsorption of glucose and inducing glycosuria. This “hybrid” diuretic effect, which couples natriuresis with osmotic diuresis, potentially leads to systemic RAAS activation. However, the association between SGLT2-i and systemic RAAS activation is not straightforward. Available data indicate that SGLT2-i cause plasma renin activity (PRA) increase in the early phase of treatment, while PRA and aldosterone levels remain unchanged in chronic treated patients. Furthermore, emerging studies provide evidence that SGLT2-i might have an interfering effect on aldosterone/renin ratio (ARR) in patients with T2DM, due to their diuretic and sympathoinhibition effects. The cardio- and reno-protective effects of GLP-1-RA are at least in part related to the interaction with RAAS. In particular, GLP1-RA counteract the action of angiotensin II (AGII) inhibiting its synthesis, increasing the inactivation of its circulating form and contrasting its action on target tissue like glomerular endothelial cells and cardiomyocytes. Furthermore, GLP1-RA stimulate natriuresis inhibiting Na+/H+ exchanger NHE3, which is conversely activated by AGII. Moreover, GLP1 infusion acutely reduces circulating aldosterone, but this effect does not seem to be chronically maintained in patients treated with GLP1-RA. In conclusion, both SGLT2-i and GLP1-RA seem to have several effects on systemic and local RAAS, though additional studies are needed to clarify this relationship.